Primary immunodeficiency and the microbiome - Maryam Ali Al-Nesf (16328649) (2021)
Purpose of review  The current understanding of the relationship of the microbiota to clinical manifestation in patients with primary immunodeficiency, specifically the inflammatory processes caused by or that result in microbial dysbiosis, and their potential therapeutic options in primary immunodeficiency diseases (PID), is the basis of this review. Recent findings  PIDs are heterogeneous diseases with variable presentations, genetic backgrounds, complications, and severity. The immune-mediators may be extrinsic, such as therapeutic regimens that patients are on, including immunoglobin, biologics, antibiotics and diet, or intrinsic, like cytokines, microRNA and microbiome. The microbiome in PID, in particular, appears to play a crucial role in helping the host's immune system maintain hemostatic control in the intestine. Many of the clinical manifestations and complications of PID may be attributed to inflammatory and immune dysregulatory processes connected to the imbalances of the diet-microbiota-host-immunity axis, as shown by data pointing to the loss of microbial diversity, dysbiosis, in PID. Summary  The gut microbiome is a promising area of study in PID. Although the connection of the microbiome to humoral immunodeficiency is evident, the possibility of utilizing the association of humoral and cellular immunodeficiency and the microbiome for therapeutic benefit is still under investigation. Other Information Published in: Current Opinion in Pediatrics License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1097/mop.0000000000001067